Prevalence and Etiology of Ocular Morbidity in Maritime Environments: A Systematic Review and Meta-Analysis of Passenger and Crew Data - Iska Novi Udayani; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita; I Made Ady Wirawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The maritime environment constitutes a unique epidemiological enclosure characterized by isolation, specific occupational hazards, and distinct environmental stressors including hyper-salinity and high ultraviolet (UV) albedo. While gastrointestinal and respiratory outbreaks at sea are well-documented, the burden of ocular morbidity remains under-quantified. This study aims to determine the prevalence and etiology of ocular emergencies, stratifying risks between industrial seafarers (crew) and recreational travelers (passengers). Methods: A systematic review and meta-analysis were conducted following PRISMA 2020 guidelines. Data were extracted from eight observational studies (2014–2024) covering expedition cruises, commercial shipping, and leisure voyages. To address population heterogeneity, a stratified analysis was performed: Track A analyzed occupational trauma in crew, while track B analyzed environmental morbidity in passengers. A random-effects model was used to calculate pooled proportions with 95% Confidence Intervals (CI), accompanied by a leave-one-out sensitivity analysis. Results: The dataset represented a combined population of over 5,000 maritime subjects. The pooled prevalence of ocular involvement in maritime trauma cases was 18.4% (95% CI: 12.1%–25.5%). Etiological analysis of crew injuries revealed a dominance of mechanical trauma, specifically metallic foreign bodies (40.5%), followed by chemical burns (26.2%). In contrast, passenger morbidity was driven by environmental factors (photokeratitis, dry eye) and infectious conjunctivitis. Conclusion: Ocular emergencies represent a significant, preventable burden in maritime travel, with distinct risk profiles for crew and passengers. The high rate of occupational trauma suggests a failure in personal protective equipment (PPE) compliance, while the environmental burden reflects the dry ship phenomenon. Mandatory protective eyewear policies and the integration of anterior-segment tele-ophthalmology are critical interventions.